2001
DOI: 10.1016/s0896-6273(01)00264-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor/Scatter Factor Is a Motogen for Interneurons Migrating from the Ventral to Dorsal Telencephalon

Abstract: Cortical interneurons arise from the proliferative zone of the ventral telencephalon, the ganglionic eminence, and migrate into the developing neocortex. The spatial patterns of migratory interneurons reflect the complementary expression of hepatocyte growth factor/scatter factor (HGF/SF) and its receptor, MET, in the forebrain. Scatter assays on forebrain explants demonstrate regionally specific motogenic activity due to HGF/SF. In addition, exogenous ligand disrupts normal cell migration. Mice lacking the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
288
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(299 citation statements)
references
References 48 publications
8
288
1
2
Order By: Relevance
“…Several of the methylation CpG sites are next to AT-runs that are high affinity sites for MeCP2. 33 In conclusion, epigenetic defects in autism samples may lead to the overlapping phenotypes with RTT and AS.…”
Section: Role Of Phosphorylation In Regulation Of Mecp2 Functionmentioning
confidence: 92%
“…Several of the methylation CpG sites are next to AT-runs that are high affinity sites for MeCP2. 33 In conclusion, epigenetic defects in autism samples may lead to the overlapping phenotypes with RTT and AS.…”
Section: Role Of Phosphorylation In Regulation Of Mecp2 Functionmentioning
confidence: 92%
“…Recent studies by our group and others revealed that MET also contributes to development of the cerebral cortex (25,26) and cerebellum (27), both of which exhibit developmental disruptions in autism (28,29). Hypomorphic MET͞HGF signaling in the cerebral cortex results in abnormal interneuron migration from the ganglionic eminence and reduced interneurons in the frontal and parietal regions of cortex (25,26). Hypomorphic MET͞HGF signaling in the cerebellum causes decreased proliferation of granule cells and a concomitant reduction in the size of the cerebellum, particularly in the vermis (27).…”
mentioning
confidence: 88%
“…MET signaling contributes to immune function (20)(21)(22) and gastrointestinal repair (18,23,24). Recent studies by our group and others revealed that MET also contributes to development of the cerebral cortex (25,26) and cerebellum (27), both of which exhibit developmental disruptions in autism (28,29). Hypomorphic MET͞HGF signaling in the cerebral cortex results in abnormal interneuron migration from the ganglionic eminence and reduced interneurons in the frontal and parietal regions of cortex (25,26).…”
mentioning
confidence: 99%
“…Hepatocyte growth factor (HGF) activates the c-Met receptor, leading to the formation of matrix metalloproteinases (15) that digest collagen and other extracellular components of the interstitium, facilitating cell migration and homing in the brain (16) and other organs. Importantly, HGF enhances vessel growth and favors cell-extracellular matrix interaction, which may be critical during myocardial regeneration after infarction.…”
mentioning
confidence: 99%